Political Orientation and Public Attributions for the Causes and Solutions of Physical Inactivity in Canada: Implications for Policy Support - Yun, Lira; Vanderloo, Leigh M.; Berry, Tanya R.; Latimer-Cheung, Amy E.; O'Reilly, Norm; Rhodes, Ryan E.; Spence, John C.; Tremblay, Mark S.; Faulkner, Guy (Frontiers in Public Health, 2019)
Objectives: To examine how public attributions for the causes and solutions of physical inactivity and individuals' self-identified political orientation are associated with support for different policy actions in addressing physical inactivity. Methods: A secondary data analysis was conducted with a sample of 2,044 Canadian adults. Two sets of 2 X 3 analyses of variance and post-hoc analyses were conducted to assess (1) the mean differences by the causes of the issue of physical inactivity (individual, or both internal and external/external) and political orientation (liberal, centrist, and conservative), and (2) responsibility for solutions (private matter, or both private and public health matter, and /public health matter) and political orientation on support for least, moderate, and most intrusive policy actions. Results: No interaction effects existed between causal attribution and political orientation on policy support, but a main effect of causal attributions for physical inactivity and political orientation was significant. Those who held internal attributions for the cause of physical inactivity showed less support for policies compared to those who held external causal attributions or both internal and external causal attributions. Conservative individuals reported the least support for all policy actions in comparison to liberal or centrist orientations. There were interaction effects between responsibility for solutions and political orientation on policy support. Conservative individuals who perceived the responsibility for solving physical inactivity as a private matter had less support for all three policy actions. Conclusions: Public acceptance of policy actions addressing physical inactivity varies by the attributions the public have regarding causes and responsibility for solving the problem, and by political orientation. Advocacy and messaging for policy implementation in the physical activity arena needs to be communicated in ways that encourage reflective and informed deliberation that is representative of the Canadian population.